Post-feminism at work?: the experiences of female journalists in the UK - Williams, Anna Louise (2010)
Within the UK recent research has suggested that a belief in gender equality is becoming increasingly prevalent. Women are frequently framed as empowered individuals who are now enjoying a freedom to choose in every aspect of their lives, placing them on equal terms with men. From this perspective, feminism is consequently viewed as outdated and redundant. Such ideas have been labelled as ‘post-feminist’ by feminists and cultural theorists. However, as many feminists have argued, whilst considerable advances have been made, women in the UK are in fact far from experiencing ‘true’ gender equality.